A five years review of transfers of suspected cardiac defects through West of Scotland neonatal transport service. (24th May 2012) - Daspal, S; Jackson, L
Abstract : Aim: To review the demographic and clinical details of infants transferred with suspected cardiac disease by a national neonatal transport team. Method: A retrospective review of suspected/confirmed cardiac transfers to and from a national cardiology service between Aug-2006 and Jul-2011. Information was collated from transport logs, referral letters and cardiology database. Data was analysed by using descriptive statistics. Results: A total 282 infants were transferred with a wide variation of gestational age (27+6 wks -47+3 wks). Age at transfer varied between 1-123 days (Mean 3 days). Following the implementation of regional antenatal referral pathways a change in referring hospital was noted with the elective deliveries occurring in a designated tertiary perinatal centre (p value 0.0002). 249 infants (88% of total) had cardiac pathology confirmed at the tertiary centre with 33 infants (12%) had normal examination on echocardiography. On 23 occasions (8.1%) was use of telemedicine service documented. 139 infants had suspected duct dependant lesions, of these 113 infants (81%) received prostin therapy at transfer (p value 0.02, considering all suspected duct dependant lesions should have been transferred on prostin). From 2009 a trend to smaller doses of prostin (<10 ng/kg/min) was noted together with increased number of antenatal diagnosis (Correlation coefficient-0.99). Respiratory support was required in 90 transfers (Ventilation-60, CPAP-8, Nasal Prong oxygen-22). Although different modes of ventilation were used prior to transfer (CMV-34, SIMV-16, PTV-10), none of the referring units used adjuncts to control CO2 clearance. End-tidal CO2 was monitored during transfer in 46 ventilated infants with a range of 2.4-11.5 KpA, mean of 5.7 kpA (CI-0.47). Conclusion: Our data confirms a recognised association between antenatal diagnosis of cardiac defects and a reduced requirement of prostin therapy. The importance of avoiding hypocarbia in such infants is now being reinforced to referring units, as is the need to commence prostaglandin therapy if a duct dependant lesion is suspected. Carbon dioxide monitoring should be standard practice when transferring ventilated cardiac infants. The benefits of the telemedicine service need to be highlighted and increased utilisation prior to transfer should be encouraged.